Novel Synthesis Method and Characterization of Porous Calcium Hexa‐Aluminate Ceramics. Issue 9 (24th July 2014) - Liu, Xueyin; Yang, Dexin; Huang, Zhaohui; Yi, Shuai; Ding, Hao; Fang, Minghao; Zhang, Shaowei; Liu, Yan‐gai; Sako, E.
<x xml:space="preserve">Abstract</x> Porous calcium hexa‐aluminate (CA6) ceramics were in‐situ synthesized by heated CaCO3 and α‐Al2O3 in a NaCl‐based salt at 1400°C for 3 h, and then characterized by X‐ray diffraction (XRD), scanning electron microscopy, (SEM) and mercury porosimetry. The size and morphology of the CA6 crystals and pores were gradually changed with the increase of NaCl addition in the raw material, indicating that the molten salt not only provided a liquid environment for synthesis of CA6, but also generated considerable pores.